STRATEGI KOMISI PENYIARAN INDONESIA DAERAH (KPID) PROVINSI BENGKULU DALAM MENSOSIALISASIKAN LITERASI MEDIA UNTUK MEWUJUDKAN PENYIARAN SEHAT - selviayana, dea; Eti Efrina (Fakultas Agama Islam Universitas Muhammadiyah Bengkulu, 2024)
The Regional Indonesian Broadcasting Commission (KPID) is an independent body established in each province of Indonesia to oversee broadcasting activities. In Bengkulu Province, one of KPID's responsibilities is to educate the public to reduce the negative impacts of broadcasting. Poor-quality broadcasting can hinder human resource development, especially among the youth, creating challenges related to the investment in human resources and its effects. This research aims to examine the communication strategy used by KPID Bengkulu to promote media literacy for fostering healthy broadcasting. The study employs a qualitative descriptive approach, gathering data through observation, interviews, and documentation. The findings reveal that KPID's efforts in media literacy socialization are focused on achieving healthy broadcasting. The commission has created a research team to evaluate the impacts of broadcasting from different media on the community. Socialization efforts regarding media literacy by KPID Bengkulu were carried out through direct involvement in media literacy programs and P3SPS initiatives. Keywords: Communication Strategy, Socialization, Media Literacy, Healthy Broadcasting, Regional Indonesian Broadcasting Commission.